Dynamic electrical stimulation for competitive progress: application technology and benefits - Rostovtsev, V. L.; Grushin, A. A. (Theory and Practice of Physical Culture, 2017)
The article summarises the experience of dynamic electrical stimulation method application in an athletic training process. The study was designed on a phased basis since 1980ies till now and has demonstrated undoubted benefits of the method as verified by arrays of skiers` performance data and the competitive success rates in cross country skiing and biathlon comprising an integrated progress indicator. A modern version of the method includes "intelligent trunks" equipped with sensors to record the thigh movements by spatial and temporal characteristics and rate individual competitive fitness by a set of performance criteria with automatic registration of a variety of energy supply rates (physical, functional, cardiovascular, neuromuscular and hormonal ones) in the stereotyped movement sequence. The method gives the means to rate current special fitness, fix the moment of maximum tension of the musculus quadriceps femoris and apply the electrical stimulation impulses to the muscle group in the push-off phase. At the present juncture, the method is applicable in a variety of versions: for ski rollers, skies, skiing stride mimicking run practices, exercise bicycle and racing bicycle, roller and classical skates and in running, walking and jumping practices.